APLIKASI KOMPOS BATANG PISANG PADA MEDIA GAMBUT UNTUK MENINGKATKAN PERTUMBUHAN BIBIT KOPI ROBUSTA - sopiana sopiana; Rosmalinda Rosmalinda; Tardi Kurniawan (Politeknik Negeri Ketapang, 2026)
Efforts to improve the quality of peat soil to become a more productive medium can be done by providing banana stem compost because it contains macro nutrients that are very much needed by plants. This study aims to determine the role of banana stem compost in peat media to increase the growth of robusta coffee seedlings. This study was conducted at the experimental garden on Jalan Rangga Sentap II, Ketapang Regency, West Kalimantan, from March to June 2024. This study used a non-factorial completely randomized design (CRD) consisting of 6 treatment levels and 4 replications so that there were 24 experimental units, where each replication consisted of 3 plants so that 72 samples were obtained. The treatments were P0: Without banana stem compost, P1: 650 g polybag-1, P2 :700 g polybag-1, P3: 750 g polybag-1, P4: 800 g polybag-1, P5: 850 g polybag-1. Observation parameters included seedling height, stem diameter, number of leaves, root length, and dry weight of seedlings. The data obtained were analyzed statistically by Analysis of Variance (ANOVA). Data showing a significant effect were further analysed using Duncan’s Multiple Range Test (DMRT) at the 5% significance level. The application of banana stem compost to peat-based growing media had a significant effect on the growth of Robusta coffee seedlings. A dose of 850 g polybag-1 of banana stem compost per polybag was found to be the most effective dose for enhancing the growth of Robusta coffee seedlings in peat-based growing media.